Simulation and Experiments of the Water Hammer Phenomenon in the Piping System - Abdul Aziz, Irvan
Transient fluid flow is closely related to a pressure increase phenomenon called water hammer. This phenomenon will be very dangerous and can damage the piping component if not taken seriously. Water hammer can be caused by a variety of factors, including valve closure and sudden pump shutdown. One way to find out more about water hammer is by conducting experiments. Retrieval of data is done by testing on a tool called Pipe Surge/Water Hammer. Then, the simulation will be done using a software called Bentley Hammer V8i. This software uses the characteristic method in solving problems related to transient flow in a piping system. Data retrieval is done by using two sensors. Sensor 1 and sensor 2 are located 20 cm and 120 cm from the solenoid valve. From the test results, for sensor 1, the maximum pressure value is 128,472 Pa and the minimum pressure is -18,040 Pa. Meanwhile, for sensor 2, the maximum pressure value of 128,472 Pa and the minimum value of -18,444 Pa are obtained. Then, from the simulation results obtained a maximum pressure value of 148,698 Pa and a minimum of -97,769 Pa for sensor one. Whereas for sensor 2 the maximum pressure value is 111,047 Pa and the minimum pressure value is -65,059 Pa.